Biohydrogen in a circular bioeconomy: A critical review. (December 2022) - Ubando, Aristotle T.; Chen, Wei-Hsin; Hurt, Dennis A.; Conversion, Ariel; Rajendran, Saravanan; Lin, Sheng-Lun
Graphical abstract: Highlights: The utilization of a circular bioeconomy framework to produce biohydrogen is reviewed. Waste valorization and biomass conversion into biohydrogen are viable pathways. Biorefinery presents a sustainable approach to generating biohydrogen. Microalgae have continued to attract considerable interest in making biohydrogen. The sustainability assessment of biohydrogen is essential for commercialization. Abstract: Hydrogen produced from biomass feedstocks is considered an effective solution in moving toward a decarbonized economy. Biohydrogen is a clean energy source that has gained global attention for adoption as it promises to mitigate climate change and human environmental damage. Through the circular economy framework, sustainable biohydrogen production with other bioproducts while addressing issues such as waste management is possible. This study presents a comprehensive review of the various biomass feedstocks and processing technologies associated with biohydrogen generation, as well as the possible integration of existing industries into a circular bioeconomy framework. The currently standing challenges and future perspectives are also discussed.